May trust and solidarity defy food scares? The case of Parmigiano-Reggiano PDO sales in the aftermath of natural disaster. Issue 12 (18th September 2019) - Menozzi, Davide; Finardi, Corrado
Abstract : Purpose: A major earthquake and aftershocks have hit the North-East part of Italy in May 2012, and caused 26 deaths and diffuse economic damage in the localised agri-food system (LAFS) of Parmigiano-Reggiano protected designation of origin (PDO), including several dairy warehouses. In the broad mobilization to help the stricken people, the LAFS actors played a primary role, giving rise to the sales of "Parmigiano-Reggiano damaged by the earthquake" (PR-T). The purpose of this paper is to investigate the main determinants of PR-T purchasing using the theory of planned behaviour (TPB). Design/methodology/approach: A survey on 200 consumers was performed. Data were collected with face-to-face interviews in stores and markets where the PR-T has been sold, and analyzed by structural equation modelling. Findings: The TPB model predictors accounted for 52 per cent of the variance of intentions to purchase PR-T in the future and 21 per cent of the variance of behaviour. Perceived behavioural control is the main predictor of intention and behaviour, indicating that making easier the access to key resources and increasing people's capability seems a major aspect to reach the intended goals. Trust in producers and retailers communication, positive image of the PDO label, sense of belonging to the region of origin and socio-demographics, i.e. age and educational levels, are correlated with intention and behaviour. The food scare flare up in the media was not a reason impeding purchasing PR-T. Originality/value: These findings show the solidarity aspects underlying the collective purchases of PR-T in the aftermath of the 2012 earthquake waves, and the importance of increasing people's capability and trust to reach the goal of facing dreadful food scares effectively.